Service Design Study of Pediatric Clinic - Yii, Li Min (Universiti Malaysia Sarawak (UNIMAS), 2017)
This study is to improve the services of local pediatric clinic in Kuching. The problem is observed through one of the service design method that is journey map technique. It is used to analyze the human (patient and visitor) behavior when they visit the pediatric clinic. The results from this investigation have led to the design of mobile apps, product merchandising, clinic environment and ambiance, and branding. This research may improve the quality and efficiency of clinic service. Thus, for this study a brand new pediatric clinic was designed.